2007
DOI: 10.1093/ajcn/85.6.1565
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of daily and monthly high-dose calciferol in vitamin D–deficient nulliparous and lactating women

Abstract: Oral vitamin D2 supplementation with 2000 IU/d or 60,000 IU/mo for 3 mo was safe, and it increased serum 25(OH)D concentrations significantly; however, only a small proportion of the women studied achieved concentrations of >or=50 nmol/L. This suggests that, when sunlight exposure is limited, doses of vitamin D2 higher than those currently studied may be needed. Monthly dosing appears to be a safe and effective alternative to daily dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 30 publications
5
74
0
Order By: Relevance
“…Recent supplementation studies have involved non-pregnant participants. Serum 25OHD was significantly increased by administration of 60 000 U of vitamin D2 per month for 3 months in lactating women (Saadi et al, 2007). However, levels 450 nmol/l were achieved only in 30% participants.…”
Section: Discussionmentioning
confidence: 85%
“…Recent supplementation studies have involved non-pregnant participants. Serum 25OHD was significantly increased by administration of 60 000 U of vitamin D2 per month for 3 months in lactating women (Saadi et al, 2007). However, levels 450 nmol/l were achieved only in 30% participants.…”
Section: Discussionmentioning
confidence: 85%
“…As described in the literature, keeping vitamin D levels in the normal range appears to require not waiting to intervene until levels fall below 75 nmol/L For example, in a study performed in the United Arab Emirates, Saadi et al reported a high prevalence of vitamin D deficiency (mean level of 19 nmol/L at inclusion) and also confirmed the importance of vitamin D supplementation in patients that are rarely exposed to the sun [9].…”
Section: Correction Of the Deficiency And Preservation Of The Levelmentioning
confidence: 84%
“…A bibliographic review by Vieth showed that hypercalcemia is always accompanied by serum vitamin D levels higher than 220 nmol/L [7][8][9][10][11].…”
Section: Innocuity Of Vitamin Dmentioning
confidence: 99%
“…Majority of women who are deficient in vitamin D, are advised to take treatment for 4-6 weeks, either with cholecalciferol 20 000 IU a week or ergocalciferol 10 000 IU twice a week, followed by standard supplementation. 24,25 The women who require short-term repletion, 20 000 IU weekly appears to be an effective and safe treatment of vitamin D deficiency. A daily dose is likely to be appropriate to maintain subsequent repletion (1000 IU daily).…”
Section: Discussionmentioning
confidence: 99%